Blue eyes - Charyn, Jerome, 1937- (Isaac Sidel, 2003)
Set in a shocking New York underworld populated by a constellation of punks, low lifes, thugs, nymphs, vice lords and bag men, Blue Eyes is the second book in Jerome Charyn's classic Isaac Quartet.Manfred 'Blue Eyes' Coen is a cop on loan to the First Deputy's office, sent to the mean streets of his old Bronx neighbourhood to do some very dirty business.Child brides are being kidnapped and are turning up in Mexico, and the daughter of a millionaire has gone missing.Are Coen's childhood friends, the Guzmanns, the key to this mystery?Coen's mentor, the disgraced First Deputy, Isaac Sidel, knew that there was only one man for the job.So, caught between his childhood loyalties and his reputation as the toughest, sharpest cop in New York City, it's up to Blue Eyes to solve the case.But too many people are double-crossing him - and too many people want him dead